Pharmacogenetic Determinants of Carbamazepine Response in Pediatric Epilepsy: Association of ABCB1, SCN1A, and UGT2B7 Gene Polymorphisms in a Kazakh Population (Bangladesh Journal of Medical Science, 2026)
Background Interindividual variability in response to carbamazepine remains a major challenge in epilepsy management, with pharmacoresistance affecting up to one-third of patients. Genetic polymorphisms influencing drug transport, metabolism, and neuronal excitability may contribute to this variability. Objective To evaluate the association between polymorphisms in ABCB1 (rs1045642), SCN1A (rs2298771, rs3812718), and UGT2B7 (rs28365063) genes and clinical response to carbamazepine in pediatric epilepsy patients of Kazakh ethnicity. Methods A case–control study was conducted including 363 children with epilepsy and 240 age- and sex-matched controls. Genotyping was performed using PCR-based methods. Clinical outcomes included seizure frequency, pharmacoresistance, and adverse drug reactions. Associations were assessed using χ² tests and multivariate logistic regression. Results A significant association was observed for ABCB1 rs1045642 (p < 0.001), with the GG genotype conferring an increased risk of pharmacoresistance (AOR = 2.87; 95% CI: 1.74–4.73). The AG genotype was also associated with increased risk (AOR = 1.67; p = 0.011). For SCN1A rs2298771, overall significance was not reached; however, one genotype demonstrated a protective effect (AOR = 0.296; p = 0.033). No statistically significant associations were identified for SCN1A rs3812718 and UGT2B7 rs28365063. Conclusion The ABCB1 rs1045642 polymorphism is a significant predictor of carbamazepine resistance in pediatric epilepsy. These findings support the integration of pharmacogenetic profiling into individualized treatment strategies.Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 865-870